Deciphering Assumptions in Lawmaking: Towards a More Human-Centric Approach (European Journal of Behavioral Sciences, 2024)
This study investigates the assumptions legislators make about the recipients of laws, drawing parallels with the homo oeconomicus model. We question whether laws are crafted under the belief that recipients are instrumental rational individuals who strive to maximize profit and minimize or evade penalties. Key objectives include evaluating the influence of these assumptions on lawmaking and determining how a shift in these beliefs may impact the law itself. The research methodology combines an analysis of Polish and American court rulings and judicial models. The study argues for the necessity of a paradigm shift, recognizing that legal subjects do not always act logically or rationally. Our research concludes that recognizing the behavioral nuances in law recipients could lead to more effective lawmaking, introducing behavioral laws and regulatory tools better suited to average, not always rational, recipients.